2021
DOI: 10.1093/infdis/jiab174
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Immune Complexes May Contribute to Neutrophil Activation in the Course of Severe Coronavirus Disease 2019

Abstract: Severe COVID-19 is associated with an overactive inflammatory response mediated by macrophages. Here, we analyzed the phenotype and function of neutrophils in COVID-19 patients. We found that neutrophils from severe COVID-19 patients express high levels of CD11b and CD66b, spontaneously produce CXCL8 and CCL2 and show a strong association with platelets. Production of CXCL8 correlated with plasmatic concentrations of LDH and D-dimer. Whole blood assays revealed that neutrophils from severe COVID-19 patients sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Fluorescence minus one (FMO) controls for CD4, CD62p, CD42b and CD41 are shown in Figure S1D. Similar results were obtained when aggregation between platelets and monocytes was analysed (Figure S1E) and also with polymorphonuclear cells, as reported previously by our group 24 . CD4 + T cell–platelet aggregates frequency showed negative correlation with lymphocyte and neutrophil counts, and positive correlation with neutrophil:lymphocyte ratio but not with leukocyte or platelet counts (Figure 1C–G).…”
Section: Resultssupporting
confidence: 86%
“…Fluorescence minus one (FMO) controls for CD4, CD62p, CD42b and CD41 are shown in Figure S1D. Similar results were obtained when aggregation between platelets and monocytes was analysed (Figure S1E) and also with polymorphonuclear cells, as reported previously by our group 24 . CD4 + T cell–platelet aggregates frequency showed negative correlation with lymphocyte and neutrophil counts, and positive correlation with neutrophil:lymphocyte ratio but not with leukocyte or platelet counts (Figure 1C–G).…”
Section: Resultssupporting
confidence: 86%
“…The potential impact of immune complexes on pathogenicity in COVID-19 was proposed [ 36 ] based on histopathology findings in the lung tissues that revealed features associated with IC mediated vasculitis including infiltration of monocytes and lymphocytes within and around blood vessels, vascular wall thickening, and focal hemorrhage [ 37 , 38 ]. In support of this notion, increased levels of CoV-2 spike-IgG ICs in the sera of COVID-19 patients was recently shown to correlate with disease severity [ 20 ]. Our study agrees with recent reports that demonstrated that IC of SARS CoV-2 virions with purified anti-spike IgG or with sera from patients with severe disease triggered increased production of proinflammatory cytokines (IL-6, TNF-α, and IL-1β) in monocytes [ 39 ] and in M2 macrophages [ 40 ].…”
Section: Discussionmentioning
confidence: 89%
“…Recently, elevated levels of spike-IgG immune complexes (ICs) were reported in sera from patients with severe COVID-19 disease [ 20 ]. To explore whether spike-IgG ICs can induce PGE2 and inflammatory cytokines in monocytes, we initially tested spike-specific chimeric monoclonal antibody (MAb) combining the mouse variable region (S-cIgG) specific for CoV-2 spike with the human IgG-Fc domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet‐activating CIC are found in all severely ill COVID‐19 patients but not mild cases. [ 95 , 96 , 97 ] Notably, neither molecular mimicry theory nor bystander theory predicts the formation of CIC. Complementary antibodies will, in turn, target molecularly complementary host antigens of which many examples exist in Tables 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%